2020
DOI: 10.1038/s41598-020-64164-4
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy rates after slow-release insemination (SRI) and standard bolus intrauterine insemination (IUI) – A multicentre randomised, controlled trial

Abstract: This multicentre, randomised, controlled cross-over trial was designed to investigate the effect of intrauterine slow-release insemination (SRI) on pregnancy rates in women with confirmed infertility or the need for semen donation who were eligible for standard bolus intra-uterine insemination (iUi). Data for a total of 182 women were analysed after randomisation to receive IUI (n = 96) or SRI (n = 86) first. The primary outcome was serological pregnancy defined by a positive beta human chorionic gonadotropin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Previous reports showed that a slow-release intrauterine insemination might improve the pregnancy rate compared to bolus IUI. In these studies, a commercially available product was used (Grasby auto-syringe driver or the EVIE Slow-Release Insemination Pump) (Muharib et al, 1992;Marschalek et al, 2017Marschalek et al, , 2020.…”
mentioning
confidence: 99%
“…Previous reports showed that a slow-release intrauterine insemination might improve the pregnancy rate compared to bolus IUI. In these studies, a commercially available product was used (Grasby auto-syringe driver or the EVIE Slow-Release Insemination Pump) (Muharib et al, 1992;Marschalek et al, 2017Marschalek et al, , 2020.…”
mentioning
confidence: 99%
“…Moreover, results of a multicentre, randomised controlled trial, comparing bolus IUI with SRI with duration of 4 hours, were recently reported by the same authors, using the same EVIE device (Marschalek et al, 2020). At total of 182 women were randomised to receive bolus-IUI (n = 96) or SRI (n = 86).…”
Section: Outcome Results Period 1 (Bolus Iui) Versus Period 2 (Modifi...mentioning
confidence: 99%
“…Previous reports showed that a slow-release intrauterine insemination (SRI) might improve the pregnancy rate when compared to bolus IUI. In these studies, a commercially available product was used (Grasby auto-syringe driver or the EVIESlow- Release Insemination Pump) ( Muharib et al, 1992 ; Marschlek et al, 2017 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports had shown that a slow-release IUI might improve the pregnancy rate compared with bolus IUI (5,6). We compared ongoing pregnancy rates after bolus IUI versus patient-friendly slow-release IUI.…”
Section: Pro (Ivf): Couples With Unexplained Infertility Should Be Rementioning
confidence: 99%